Efficiency and Effectiveness of Alternative Dispute Resolution Schemes Towards the Promotion of Access to Justice in Bangladesh - Islam, Mohammad Saidul (IIUC Studies, 2014)
In recent years in Bangladesh there has been renewed emphasis on the Alternative Dispute Resolution schemes as a means to avoid the use of contested hearings in the formal litigation and to ensure the most fundamental right of access to justice for all in an easy way. These Alternative Dispute Resolution (ADR) modalities are considered as less likely to fuel the parental conflicts, more likely to induce the parties to resolve their conflicts in an amicable manner preserving the future relationship between the parties and reducing cost, delay and loss of energy to a significant extent. Following the considerable advantages of ADR almost every county of the world has introduced ADR system in its justice delivery system which has paved the way to the promotion of access to justice indiscriminately for all. This paper is an attempt to provide a comprehensive idea about obstacles in the way of access to justice in our legal system and by analyzing the different mechanisms of ADR and court and non-court based practices of those modalities under different legislations of Bangladesh, to show the fairness, efficiency and effectiveness of ADR towards the promotion of access to justice and to provide some recommendations for the complete success of ADR towards the effective, non-discriminative, speedy and easy access to justice for all either rich or poor, literate or illiterate, male or female and elite or lower class. DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20405 IIUC Studies Vol.8 December 2011: 95-112